(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Communication plays a vital role in our daily lives, and language proficiency is crucial for effective communication. In the field of language education, the concept of communicative competence has been a focal point in the teaching and assessment of language for specific purposes. This article examines the historical view on communicative competence and its significance in language education.